Research of medicinal products of the nsaid of the pharmaceutical market in Ukraine for the period 2014-2018 - L. V. Iakovlieva; A. A. Titova (The State Expert Center of the Ministry of Health of Ukraine, 2019)
Nonsteroidal Anti-Inflammatory Drugs (NSAIDs) are groups of different chemical structures of drugs (derivatives of acids) that are widely used in clinical practice. More than three million people in the world take NSAIDs every day. The aim of the study - аnalysis of the range and target characteristics of nonsteroidal anti-inflammatory drugs in the Ukrainian pharmaceutical market during 2014-2018. Nonsteroidal anti-inflammatory drugs, presented on the pharmaceutical market of Ukraine for 2014-2017, were selected as research objects. The research used retail prices, according to the «Pharmstandard» system of the «Morion» company. NSAIDs in Ukraine during 2014-2018 were represented from 302 to 419 TN based on 32 INN. Diclofenac was also represented by the largest number of trade names, due to its distinct efficacy, less toxicity among the most effective drugs and the low cost of domestic generic drugs. Fewer TN than Diclofenac but more than the bulk of NSAIDs in the market were presented by the following INNs - meloxicam, ibuprofen, nimesulide and a combination of glucosamine with chondroitin sulfate. A large selection of NSAIDs has been identified in the pharmaceutical market of Ukraine. Imported Nonsteroidal anti-inflammatory drugs are more represented. These drugs have a wide range of prices that allow you to optimize your treatment costs. The prices of NSAIDs for researched period had increase. The reason can be in conditions of political and socio-economic crisis in the country